An in vitro iron superoxide dismutase inhibitor decreases the parasitemia levels of Trypanosoma cruzi in BALB/c mouse model during acute phase. Issue 3 (December 2015) - Olmo, Francisco; Urbanová, Kristína; Rosales, Maria Jose; Martín-Escolano, Ruben; Sánchez-Moreno, Manuel; Marín, Clotilde
Abstract: In order to identify new compounds to treat Chagas disease during the acute phase with higher activity and lower toxicity than the reference drug benznidazole (Bz), two hydroxyphthalazine derivative compounds were prepared and their trypanocidal effects against Trypanosoma cruzi were evaluated by light microscopy through the determination of IC50 values. Cytotoxicity was determined by flow cytometry assays against Vero cells. In vivo assays were performed in BALB/c mice, in which the parasitemia levels were quantified by fresh blood examination; the assignment of a cure was determined by reactivation of blood parasitemia levels after immunosuppression. The mechanism of action was elucidated at metabolic and ultra-structural levels, by 1 H NMR and TEM studies. Finally, as these compounds are potentially capable of causing oxidative damage in the parasites, the study was completed, by assessing their activity as potential iron superoxide dismutase (Fe-SOD) inhibitors. High-selectivity indices observed in vitro were the basis of promoting one of the tested compounds to in vivo assays. The tests on the murine model for the acute phase of Chagas disease showed better parasitemia inhibition values than those found for Bz. Compound 2 induced a remarkable decrease in the reactivation of parasitemia after immunosuppression. Compound 2 turned out to be a great inhibitor of Fe-SOD. The high antiparasitic activity and low toxicity together with the modest costs for the starting materials render this compound an appropriate molecule for the development of an affordable anti-Chagas agent. Graphical abstract: Highlights: Low toxicity alternative treatment against Trypanosoma cruzi in murine model. The acute and chronic phases of Chagas disease. In vitro evaluation against epimastigote, amastigote and trypomastigote forms. Compound 2 selectively inhibits the parasite Fe-SOD enzyme. Compound 2 should be followed-up in future clinical experiments.